REPRESENTATION OF MICHEL FOUCAULT’S POWER RELATION IN DECEPTION POINT BY DAN BROWN - PRATIWI, LINDA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Deception Point, Representation, Power Relation, Michel Foucault, Politic, Power/knowledge.One discussion in the theory of Power/knowledge by Foucault is the analysis of power relation which focuses on the relation in the society especially in politics. The knowledge in power relation is used to maintain power. Deception Point novel by Dan Brown published in 2001 describes the scientific discovery surprising with an ingenious deception. Nevertheless, Deception Point clearly portrays distinct political thriller in literary works that ever exist in the world. Deception Point portrays power relation between subjects and alliance.Representation of Michele Foucault’s power relation within his ideas about politics, discursive practice and power/knowledge can be portrayed in Deception Point by Dan Brown. His ideas are to interlace ‘political friendship’ become alliance. It is also as tactics or strategies to reach a political goal. Cultural studies approach is applied in this study because discussing about politic in a state. To make a reliable analysis, twelve characters are analyzed by using theory of power relation. Among twelvecharacters, there are two characters who have power. They are Senator Thomas Sedgewick Sexton and Zachary Herney. Both of them are the candidate president in U.S. According to the background above, the problem of the study is about how the power relation is portrayed in Dan Brown’s novel titled Deception Point.The result of this study shows that the power relation is found in Deception Point. There are two persons in power relation found in the novel. The First is the power relation between Senator Thomas Sedgewick Sexton with Gabrielle Ashe and Private Aero Space; the second is the power relation between Zachary Herney and Lawrence Ekstrom plus NASA, Civilian Scientists, Marjorie Tench, Rachel Sexton and William Pickering plus Delta Force. The power relation is shown by the candidates’ action and used as the strategy in the politic.The writer has the following advice to the next researchers who want to use Deception Point by Dan Brown as the material objects of analysis to analyze psychological impact of power relation done by the main characters. They can also apply power relation in sexuality and power relation in media relating to hegemony.